Does the redundancy effect exist in electronic slideshow assisted lecturing?. (October 2015) - Liu, Tzu-Chien; Lin, Yi-Chun; Gao, Yuan; Yeh, Shih-Ching; Kalyuga, Slava
Abstract: This study investigated the occurrence of the redundancy effect in a normal classroom when presenting multiple formats of information with the assistance of electronic slideshows. A virtual classroom that simulates a normal classroom was developed as the experimental platform in this study. One hundred and twenty undergraduates and graduated students were randomly assigned to the following three experimental conditions with varying presentation formats: audio only condition, visual only condition, and audio-visual condition. Test accuracy scores and cognitive load self-rating scales on both the recall and the comprehension tests were used to measure differences between various conditions. Analyses revealed a reverse audiovisual redundancy effect. For the recall test, the presentation of on-screen textual information accompanied by spoken narrations outperformed the presentation with the audio only source on test accuracy scores and indicated lower self-ratings of cognitive load. For the comprehension test, the presentation of on-screen textual information accompanied by spoken narrations outperformed the presentations with either of these two sources with higher test accuracy scores and lower cognitive load self-ratings. Classroom interference and segmented presentation were hypothesized to be two possible factors in determining the presence or absence of the redundancy effect. Highlights: Investigated the redundancy effect in electronic slideshow assisted lecturing. Used a virtual classroom that simulated a normal classroom as a research platform. A reverse audiovisual redundancy effect was obtained. Audio-visual condition resulted in the best performance among the three conditions. Audio-visual condition reported lower cognitive load than the audio only condition.